Relationship between Principal Supervision in Increasing the Job Satisfaction of Private Junior High School Teachers in East Bogor District - ., Nurjanah (Journal of Humanities and Social Studies, 2018)
In general, this study aims to examine teacher job satisfaction and variables that have a relationship with teacher job satisfaction, in this case is the supervision of the principal and efforts to improve teacher job satisfaction. The method used in this study is a survey method with a correlational approach. The research variable consists of independent variables, namely the supervision of the principal, with the dependent variable namely teacher job satisfaction. This research was conducted in private junior high schools in Bogor Timur sub-district, Bogor City. Research data collection was carried out by distributing questionnaires to 186 respondents who had been selected as samples. The results of the questionnaire were collected and recorded in order to analyze the data to test the research hypothesis and to determine the strength of the relationship between the supervision of the principal and teacher job satisfaction. To test the research hypothesis and to determine the strength of the relationship between the supervision of the principal and teacher job satisfaction, data were analyzed using statistical tests in the form of correlation and simple linear regression, and multiple correlations and regression. Hypothesis testing was carried out at significance level a = 0.05. This study yields the main conclusion that there is a positive relationship between supervision of the principal and teacher job satisfaction, meaning that the higher the supervision of the principal, the higher the teacher job satisfaction is indicated by the regression equation Ŷ=74.46+0.53X1 and the correlation coefficient ry1 = 0.520 . Based on the findings, the teacher's job satisfaction can be improved through supervision of the principal.